If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15(y+1)+5(4y-4)=4(y-4)+9
We move all terms to the left:
-15(y+1)+5(4y-4)-(4(y-4)+9)=0
We multiply parentheses
-15y+20y-(4(y-4)+9)-15-20=0
We calculate terms in parentheses: -(4(y-4)+9), so:We add all the numbers together, and all the variables
4(y-4)+9
We multiply parentheses
4y-16+9
We add all the numbers together, and all the variables
4y-7
Back to the equation:
-(4y-7)
5y-(4y-7)-35=0
We get rid of parentheses
5y-4y+7-35=0
We add all the numbers together, and all the variables
y-28=0
We move all terms containing y to the left, all other terms to the right
y=28
| 4z+29=317 | | -2x-9=0+x | | 6/8=30/x | | f÷4(-5)=-9 | | 5-4x=31 | | z–93= 2 | | 18/14=b=2/b | | 10x+4=7x+8 | | 4x-8+2x=2x-25 | | 2-15n=5(-2n+2) | | 301x-38+6=20 | | 0=38t-16t^2-22 | | 2(7-3=y) | | 7(n-2)-(6-5n)=11n | | 184=x+5x | | 2a+2=a+6 | | 3.9n+6=3(n-4) | | 0.01p+0.05p+0.25(4p)+0.1(4p+3)=6.14 | | 11g+5=82 | | 9(x+5)=2(x-7)+5(x+) | | 2^h=8^2 | | 3x-2x+x-10=2(x-5) | | 2-r/3=8 | | x^2-15x^2+34=0 | | 0=5k-3(1+k)9 | | 22x+20=17x-95 | | 10x+6-28x+4=-88 | | 5/x=16/21 | | 3/4=x-3/16 | | 2(x+1)=x–8 | | 10+6h-12=46 | | M-13=15+5m |